Multi-muscle electrical stimulation and stand training: Effects on standing. (4th May 2019) - Momeni, Kamyar; Ramanujam, Arvind; Garbarini, Erica L.; Forrest, Gail F.
Abstract : Objective: To examine the biomechanical and neuromuscular effects of a longitudinal multi-muscle electrical stimulation (submaximal intensities) training of the lower limbs combined with/without activity-based stand training, on the recovery of stability and function for one individual with spinal cord injury (SCI). Design: Single-subject, longitudinal study. Setting: Neuroplasticity laboratory. Participant: A 34-year-old male, with sensory- and motor-complete SCI (C5/C6). Interventions: Two consecutive interventions: 61 hours of supine, lower-limb ES (ES-alone) and 51 hours of ES combined with stand training using an overhead body-weight support system (ST + ES). Outcome Measures: Clinical measures, trunk stability, and muscle activity were assessed and compared across time points. Trunk Stability Limit (TSL) determined improvements in trunk independence. Results: Functional clinical values increased after both interventions, with further increases post ST + ES. Post ES-alone, trunk stability was maintained at 81% body-weight (BW) loading before failure; post ST + ES, BW loading increased to 95%. TSL values decreased post ST + ES (TSLA/P =54.0 kg.cm, TSLM/L =14.5 kg.cm), compared to ES-alone (TSLA/P =8.5 kg.cm, TSLM/L =3.9 kg.cm). Trunk muscle activity decreased post ST + ES training, compared to ES-alone. Conclusion: Neuromuscular and postural trunk control dramatically improved following the multi-muscle ES of the lower limbs with stand training. Multi-muscle ES training paradigm of the lower limb, using traditional parameters, may contribute to the functional recovery of the trunk.